2020
DOI: 10.3390/su12062246
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital Protects Social Workers from Burnout and Secondary Traumatic Stress

Abstract: Summary: To counteract the negative consequences inherent to the emotionally demanding professions like social work, we need to advance the understanding of the resources that preserve the employees’ well-being. This study investigated the role of Psychological Capital (PsyCap) in protecting social workers from developing burnout and Secondary Traumatic Stress (STS). The design of the study builds on the job demands-resources model and the conservation of resources theory. A national sample of 193 Romanian soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 85 publications
(122 reference statements)
3
29
1
2
Order By: Relevance
“…The results of this study showed that personal accomplishment has a high and positive relationship with PsyCap [44,45] and less of a weight on burnout dimension, which seems to indicate that personal achievement, traditionally considered a subdimension of burnout, would instead be a personal resource to cope with burnout. These results support the approaches of other authors who consider that exhaustion and depersonalization are the core parts of burnout and that personal accomplishment is not a reaction to stressful situations but an individual resource (personality) that develops largely independently and so has a separate role in burnout [23].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study showed that personal accomplishment has a high and positive relationship with PsyCap [44,45] and less of a weight on burnout dimension, which seems to indicate that personal achievement, traditionally considered a subdimension of burnout, would instead be a personal resource to cope with burnout. These results support the approaches of other authors who consider that exhaustion and depersonalization are the core parts of burnout and that personal accomplishment is not a reaction to stressful situations but an individual resource (personality) that develops largely independently and so has a separate role in burnout [23].…”
Section: Discussionsupporting
confidence: 90%
“…That is, workers may come to believe that they can perform their jobs adequately and be successful in meeting their work-related goals. Thus, personal accomplishment would reflect the workers' personal characteristics and not their reactions to stressful situations [22,23] so it may be considered not a burnout dimension but an individual resource that develops largely independently of emotional exhaustion and depersonalization [21,24]. Some authors have also considered this idea and have removed the personal achievement dimension from burnout studies [23].…”
Section: Job Demands Individual Resources and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies show that PsyCap is having a significant and enduring influence on employees and their attitude towards work environments (Gibson and Hicks, 2018; Grover, Teo, Pick, Roche, and Newton, 2018; Kun and Gadanecz, 2019). It has the capability to reduce burnout (Vîrgă et al, 2020), enhance wellbeing, and resultant performance (Imran and Shahanawaz, 2020). Related to the "best self", PsyCap comprises of four componentshope, efficacy, Optimism, and Resilience (Luthans and Youssef, 2004).…”
Section: Psycapmentioning
confidence: 99%
“…The experts confirmed that a more holistic, systemic, and dynamic perspective of burnout is missing. Several studies have taken first steps in this direction, for example by identifying “positive gain spirals” [ 22 , 59 , 60 , 61 , 62 ], which in computational modeling are identified as “positive feedback loops” [ 52 ]. This can be described as the positive relationship between variables—if one variable increases or decreases (the “cause”), the other variable increases or decreases with it (the “effect”), causing the first variable to increase or decrease even more (the “feedback loop”).…”
Section: Resultsmentioning
confidence: 99%